Sildenafil Vs. Tadalafil for The Treatment of Benign Prostatic Hyperplasia: A Single-arm Self-controlled Clinical Trial - Zahir, Mazyar; Samzadeh, Mohammad; Poopak, Amirhossien; Khoshdel, Ali Reza; Armin, Arash (Urology Journal, 2023)
Purpose: To compare the efficacy and adverse events of sildenafil monotherapy for benign prostatic hyperplasia (BPH) with its FDA-approved counterpart, tadalafil. Materials and Methods: In this single-arm self-controlled clinical trial, 33 patients were enrolled. All patients underwent a 6-week treatment with sildenafil, followed by a 4-week washout period and finally a 6-week treatment with tadalafil. Patients were examined on each appointment and post-void residual (PVR) urine, International Prostate Symptom Score (IPSS) and Quality of life index (IPSS-QoL index) were recorded subsequently. Efficacy of each drug regimen was then evaluated by comparing these outcome parameters. Results: Both sildenafil and tadalafil were shown to improve PVR (both p < .001), IPSS (both p < .001) and IPSS- QoL index (both p < .001) significantly. Sildenafil was more effective than tadalafil in reducing PVR (mean difference (95%CI) = 9.91% (4.11, 15.72), p < .001) and ameliorating IPSS-QoL index (mean difference (95%CI) = 19.3% (4.47, 34.41), p = .027). Moreover, although not significant, sildenafil reduced IPSS more than tadalafil (mean difference (95%CI) = 3.33% (-0.22, 6.87), p = .065). Concurrent erectile dysfunction did not affect responsiveness to therapy with either sildenafil or tadalafil but age was inversely related to post-treatment IPSS in both sildenafil (B = 0.21 (0.04, 0.37), p = .015) and tadalafil (B = 0.14 (0.02, 0.26), p = .021) regimens with a more prominent role in responsiveness to sildenafil (β = 0.31) compared to tadalafil (β = 0.19). Conclusion: Considering the significantly better improvement of PVR and IPSS-Qol index with sildenafil, this drug can be nominated as a suitable alternative for tadalafil as a BPH treatment, especially in younger patients who don’t have any contraindications.